O palhaço pára-quedas: reflexões sobre a arte circense no município de Bauru - SP (Brasil) - Maciel, Talita Ribeiro [UNESP]; Simões, Rosa Maria Araújo [UNESP] (My University, 2013)
This biographical and bibliographical research aimed understanding the circus and its clowns. The origin of the circus is presented taking into account its earliest manifestations in ancient Greece, until the creation of the modern circus in 1970 by Englishman Philip Astley. The clown, who was introduced in 1778 only after the circus has become an essential figure in the show, coming to represent the modern circus. Here, the different types of clowns are presented and their main characteristics are shown as a way to differentiate between them. The difficulties faced by circus companies are pointed, trying to understand the reduction of circus companies. To understand the formation and transformation of the clown in his years at the profession, the Clown Pára-quedas, artist of Bauru / SP was interviewed, their stories help to unravel some of the satisfactions of the profession and the problems faced by circus performers.
Keywords: Circus; Clowns; Profession